2019
DOI: 10.1121/1.5125135
|View full text |Cite
|
Sign up to set email alerts
|

Insertion loss of asymmetrical balconies on a building façade

Abstract: The acoustical insertion loss of asymmetrical balconies on high-rise buildings was studied experimentally using a 1:3 scaled down model in the present study. Four balcony forms featured by the presence of a full-height side-wall were included. A linear loudspeaker array was adopted as the sound source. The effects of source orientation and balcony elevation angle on the insertion loss and its spectral variation were examined. The position of the full-height side-wall relative to the sound source significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Some researches opted to study the acoustic characteristics of a façade in laboratories. 37 52 Díaz and Pedrero 37 and Díaz et al 38 experimentally investigated the effect of rolling shutters and shutter boxes on the sound insulation properties of a façade window. The study contained a summary of sound insulation from airborne noise in several types of windows with a built-in shutter and prefabricated box.…”
Section: Studies On Sound Insulation Of Building Façadementioning
confidence: 99%
See 1 more Smart Citation
“…Some researches opted to study the acoustic characteristics of a façade in laboratories. 37 52 Díaz and Pedrero 37 and Díaz et al 38 experimentally investigated the effect of rolling shutters and shutter boxes on the sound insulation properties of a façade window. The study contained a summary of sound insulation from airborne noise in several types of windows with a built-in shutter and prefabricated box.…”
Section: Studies On Sound Insulation Of Building Façadementioning
confidence: 99%
“…On the other hand, owing to the large dimensions of the façade structure, some researchers have chosen to use scaled configurations to facilitate the tests. Tang et al 40 experimentally studied the insertion loss of asymmetrical balconies on a building façade with a 1:3 scaled-down model. It was shown that the position of the sound source relative to the full-height sidewall significantly affects the balcony insertion loss.…”
Section: Studies On Sound Insulation Of Building Façadementioning
confidence: 99%